2011
DOI: 10.1007/s13304-011-0075-6
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent adenoid cystic carcinoma in the liver: a repeated laparoscopic surgical approach

Abstract: Adenoid cystic carcinoma (ACC) is characterized by a particularly aggressive behavior even many years after resection of primary tumor. The evolution of metastasis dramatically affects the final outcome but resection should always be evaluated. Herein is described a case of aggressive ACC of the parotid gland in a 30-year-old female. She developed local recurrence and lung metastases; then, she also developed two liver metastasis 112 and 132 months after the resection of the primitive cancer of the parotid gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…6 These malignant tumours often have an indolent course over years but have propensity for metastasis to other organs, lungs being the commonest site followed by liver. 7,8 Spread along perineural lymphatics resulting in multiple local recurrence is unique to adenoid cystic carcinoma. Rarely, primary adenoid cystic carcinoma can also occur in other sites like breast, skin, lacrimal glands, external auditory canal, uterine cervix, upper gastrointestinal tract, lung and bones.…”
Section: Discussionmentioning
confidence: 99%
“…6 These malignant tumours often have an indolent course over years but have propensity for metastasis to other organs, lungs being the commonest site followed by liver. 7,8 Spread along perineural lymphatics resulting in multiple local recurrence is unique to adenoid cystic carcinoma. Rarely, primary adenoid cystic carcinoma can also occur in other sites like breast, skin, lacrimal glands, external auditory canal, uterine cervix, upper gastrointestinal tract, lung and bones.…”
Section: Discussionmentioning
confidence: 99%
“…However, if liver metastases were accompanied by metastases at other sites, additional factors need to be considered. The definition of resectability might not be limited to isolated liver metastases because multiple liver metastases can also be surgically treated ( 15 ), even recurrent liver metastases ( 5 ). The extent of resection and the function of the remnant liver should be considered, and a multidisciplinary team should be involved in evaluating the treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Ten patients were found to have lung metastases before liver metastases. The other 13 case reports in PubMed were reviewed in Table 2 (5,8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Clinical Characteristics Of Liver Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Scuderi et al 11 reported one case of recurrent liver metastasis that was efficiently achieved by a laparoscopic approach. The patient remained disease-free for 1 year after the surgical resection.…”
Section: Discussionmentioning
confidence: 99%